Cambridge yearbook of European legal studies, Vol. 19 2017 - Centre for European Legal Studies (CELS) (Cambridge : Cambridge University Press, 2017)
"The Cambridge Yearbook of European Legal Studies provides a forum for the scrutiny of significant issues in EU Law, the law of the European Convention on Human Rights, and Comparative Law with a 'European' dimension, and particularly those issues which have come to the fore during the year preceding publication. The contributions appearing in the collection are commissioned by the Centre for European Legal Studies (CELS) Cambridge, a research centre in the Law Faculty of the University of Cambridge specialising in European legal issues. The papers presented are at the cutting edge of the fields which they address, and reflect the views of recognised experts drawn from the University world, legal practice, and the institutions of both the EU and its Member States. Inclusion of the comparative dimension brings a fresh perspective to the study of European law, and highlights the effects of globalisation of the law more generally, and the resulting cross fertilisation of norms and ideas that has occurred among previously sovereign and separate legal orders. The Cambridge Yearbook of European Legal Studies is an invaluable resource for those wishing to keep pace with legal developments in the fast moving world of European integration. SUBSCRIPTION TO SERIES To place an annual online subscription or a print standing order through Hart Publishing please click on the link below. Please note that any customers who have a standing order for the printed volumes will now be entitled to free online access. www.hartjournals.co.uk/cyels/subs Editorial Advisory Board John Bell Alan Dashwood Simon Deakin David Feldman Richard Fentiman Angus Johnston John R Spencer Founding Editors Alan Dashwood Angela Ward."--Bloomsbury Publishing.
Includes bibliographical references and index.
Keywords: Law -- Study and teaching -- Europe; Law -- Study and teaching; Europe